Hospitalization Costs of COVID-19 Cases and Their Associated Factors in Guangdong, China: A Cross-Sectional Study - Dong, Moran; Yang, Zuyao; Chen, Yingyao; Sun, Jiufeng; Ma, Wenjun; Cheng, Shouzhen; Sun, Xiaoli; Xiao, Jianpeng; He, Guanhao; Hu, Jianxiong; Wang, Jiaqi; Chen, Guimin; et al. (Frontiers in Medicine, 2021)
Abstract Background The ongoing COVID-19 pandemic has brought significant challenges to health system and consumed a lot of health resources. However, evidence on the hospitalization costs and their associated factors in COVID-19 cases is scarce. Methods We included 876 confirmed COVID-19 cases admitted to 33 designated hospitals from January 15th to April 27th, 2020 in Guangdong, China, and collected their demographic and clinical information. A multiple linear regression model was performed to estimate the associations of hospitalization costs with potential associated factors. Results The median of total hospitalization costs of COVID-19 cases was $2,869.4 (IQR: $3,916.8). We found higher total costs in male (%difference: 29·7%, 95%CI: 15·5%, 45·6%) than in female cases, in older cases than in younger ones, in severe cases (%difference: 344·8%, 95%CI: 222·5%, 513·6%) than in mild ones, in cases with clinical aggravation than those without, in cases with clinical symptoms (%difference: 47·7%, 95%CI: 26·2%, 72·9%) than those without, and in cases with comorbidities (%difference: 21·1%, 21·1%, 95%CI: 4·4%, 40·6%) than those without. We also found lower nonpharmacologic therapy costs in cases treated with traditional Chinese medicine (TCM) therapy (%difference: -47·4%, 95%CI: -64·5% to -22·0%) than cases without. Conclusion The hospitalization costs of COVID-19 cases in Guangdong were comparable to the national level. Factors associated with higher hospitalization costs included sex, older age, clinical severity and aggravation, clinical symptoms and comorbidities at admission. TCM therapy was found to be associated with lower costs for some nonpharmacologic therapies.